STUDENTS’ SATISFACTION OF LECTURER TEACHING PERFORMANCE ONLINE AT INSTITUTE OF HOME AFFAIR GOVERNANCE (IPDN) - maisondra, maisondra (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2024)
The implementation of online learning during the Covid-19 Pandemic is a government policy in order to reduce the spread of the disease outbreak. It is not yet known to what extent it reduces the teaching performance of lecturers. This study to determine IPDN students’ satisfaction of lecturer performance in teaching online which was carried out, which was seen through four indicators, namely: 1) Teaching Preparation, 2) Discipline, 3) Interaction, and 4) Evaluation. This type of research is descriptive analysis research, which is an attempt to describe the performance of lecturers in teaching online. Data were obtained from the results of field research by distributing questionnaires in the form of asking questions directly to 160 respondents (or 10 percent of the total, 1,600 junior students) who had previously been randomly selected from junior students of IPDN. The data obtained were analyzed using qualitative analysis methods. The results showed that: Assessment for Teaching Preparation 95.5 percent, Discipline 90 percent, Interaction 80 percent, and Evaluation 94.5 percent. If we take the average score given by junior students or the satisfaction level is: 90 percent. This figure is quite high. But, the bias of this study is that the tendency of students' evaluation of lecturer performance is always to say that it is very good and good close to 100 percent. These figures do not yet show what percentage actually teaching online during the Covid-19 pandemic has reduced lecturer performance compared to teaching offline. This figure only shows the level of student satisfaction level with lecturer performance in teaching based on the four indicators above.